Development of a Counseling Package Based on the Lived Experiences of Middle School Girls for Preventing Academic Procrastination - Karevan Brojerdi, Kiyana; Shariat Bagheri, Mohammad Mahdi; Salehi, Keyvan (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Academic procrastination is a common issue among students that significantly impacts their academic performance and mental health. This study aims to develop a counseling package based on the lived experiences of middle school girls to reduce academic procrastination. Considering the multifaceted nature of procrastination, this study examines cognitive, behavioral, emotional, relational, and motivational dimensions to create an effective intervention.Methods and Materials: This qualitative study utilized a phenomenological approach to explore the lived experiences of middle school girls with academic procrastination. Participants were purposefully selected from schools in District 5 of Tehran during the 2023-2024 academic year. Data were collected through semi-structured interviews and analyzed using Colaizzi's seven-step method to extract meaningful statements, formulate their meanings, and identify themes.Results: Data analysis revealed five main dimensions in the students' lived experiences of academic procrastination: cognitive, behavioral, emotional, relational, and motivational. The cognitive dimension includes errors in understanding concepts, perceptions of the difficulty of materials, the ability to focus and pay attention, and personal attitudes and beliefs about education. The behavioral dimension encompasses avoidance behaviors, sleep and rest patterns, leisure activities, use of technology and social networks, learning styles, and academic planning. The emotional dimension involves feelings related to academic pressure, experiences of failure and frustration, motivation and enthusiasm for learning, and levels of academic stress and anxiety. The relational dimension refers to interactions with friends and teachers, family relationships, school culture and classroom environment, and the impact of virtual communications. Finally, the motivational dimension includes academic goals, intrinsic and extrinsic rewards, self-efficacy beliefs, individual and family values, previous experiences of success and failure, and the importance of education in future planning.Conclusion: The developed counseling package consists of 12 sessions addressing each identified dimension. This program includes sessions on behavioral strategies (sleep, time management), cognitive techniques (error correction, focus enhancement), emotion management (stress reduction, motivation increase), and communication skills (effective interaction with peers, teachers, and family). This comprehensive approach is designed to equip students with the necessary skills to effectively combat academic procrastination.